Relative importance of nanoflagellate grazing and viral lysis for the mortality of heterotrophic bacteria and Synechococcus spp. in a high-latitude fjord (Adventfjorden, Svalbard) during the summer - Olivia, Madeline; Shiu, Ruei-Feng; Wei-Yi Chen, Patrichka; Chang, Chia-Mei; Annabel, Clara Natalie; Ni, Chuen-Fa; Chien, Hwa; Giletycz, Slawomir Jack; Tsai, An-Yi (Polar research, 2025)
Viral lysis and grazing play crucial but distinct roles in microbial community dynamics and carbon cycling. Yet, their relative influence on the abundance of heterotrophic bacterial and picophytoplankton populations, especially in Arctic fjords, remains poorly understood. To address this knowledge gap, we conducted modified dilution experiments in Adventfjorden, Svalbard, to quantify microbial growth, grazing pressure and virus-induced mortality. Our results showed that the abundance of virus-like particles (VLP) ranged between 1.4 and 8.9 × 106 viruses ml−1, with a negative correlation to salinity. This suggests that freshwater inputs, such as meltwater, could contribute to higher VLP abundance in these waters. The VLP-to-bacteria ratio varied between 9.8 and 700.9, with a large variation below a salinity of 28 PSU and an inverse correlation with salinity. Grazing, primarily by nanoflagellates, emerged as the dominant factor in reducing heterotrophic bacterial and Synechococcus spp. populations, accounting for 12–55% and 20–110% of their production losses, respectively. This study was conducted in summer, when meltwater discharges entered coastal waters in Svalbard fjords at an extremely high rate, providing an opportunity to study microbial processes under projected future warming conditions.